2023
DOI: 10.3389/fphar.2023.1078205
|View full text |Cite
|
Sign up to set email alerts
|

Dapagliflozin alleviates myocardial ischemia/reperfusion injury by reducing ferroptosis via MAPK signaling inhibition

Abstract: Reperfusion is essential for ischemic myocardium but paradoxically leads to myocardial damage that worsens cardiac functions. Ferroptosis often occurs in cardiomyocytes during ischemia/reperfusion (I/R). The SGLT2 inhibitor dapagliflozin (DAPA) exerts cardioprotective effects independent of hypoglycemia. Here, we investigated the effect and potential mechanism of DAPA against myocardial ischemia/reperfusion injury (MIRI)-related ferroptosis using the MIRI rat model and hypoxia/reoxygenation (H/R)-induced H9C2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…A study by Jhuo et al examined myocardial mitochondrial function in HFDinduced metabolic disorders and obesity, and the authors found that empagli ozin-treated mice exhibited improved cardiomyocyte mitochondrial biogenesis function [40]. In a study on SGLT2is and ischemiareperfusion injury, Dapa was demonstrated to improve myocardial injury and cardiac function in rats by inhibiting ferroptosis by inhibiting ACSL4 and upregulating the SLC7A11/GPX4 axis and FTH [41].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Jhuo et al examined myocardial mitochondrial function in HFDinduced metabolic disorders and obesity, and the authors found that empagli ozin-treated mice exhibited improved cardiomyocyte mitochondrial biogenesis function [40]. In a study on SGLT2is and ischemiareperfusion injury, Dapa was demonstrated to improve myocardial injury and cardiac function in rats by inhibiting ferroptosis by inhibiting ACSL4 and upregulating the SLC7A11/GPX4 axis and FTH [41].…”
Section: Discussionmentioning
confidence: 99%
“…H9C2 was starved with glucose-free DMEM involving 2% FBS for 4 hours before each anoxia. As mentioned earlier, the experimental procedure of anoxia/reoxygenation (A/R) was conducted on H9C2 in order to replicate the conditions of myocardial ischemia-reperfusion [34]. Brie y, cardiomyocytes were transferred to DMEM without glucose and serum and cultivated in an anoxic incubator (containing 1%O 2 , 4% CO 2 and 95% N 2 , Heracellℱ VIOSℱ CO 2 Incubator, United States) at 37°C for 2 h. Following this, the glucose-free and serum-free medium was substituted with a conventional medium and placed in the standard incubator for a duration of 4 hours to replicate the e cacy of ischemia-reperfusion injury.…”
Section: Cell Culture and Ex Vivo Simulated Ischemia-reperfusion Therapymentioning
confidence: 99%
“…As was already said, the MI/R injury model was established and exploited [34]. SD male rats in good health were chosen, given 50 mg/kg of sodium pentobarbital to make them sleepy, and then laid down on surgery plates and held in place with leather straps.…”
Section: Animal and Experimental Protocolsmentioning
confidence: 99%
“…Myocardial infarction is the most popular primary symptom of IHD [ 3 ]. In clinical therapy, prompt reperfusion is crucial to decrease infarct size, save the ischemic myocardium, and prevent the onset of heart failure [ 1 , 4 ]. Nevertheless, reperfusion may induce myocardial injury named myocardial ischemia/reperfusion injury (MIRI) [ 4 – 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In clinical therapy, prompt reperfusion is crucial to decrease infarct size, save the ischemic myocardium, and prevent the onset of heart failure [ 1 , 4 ]. Nevertheless, reperfusion may induce myocardial injury named myocardial ischemia/reperfusion injury (MIRI) [ 4 – 6 ]. Increasing evidence reveals that reperfusion injury accounts for 50% of the approximate myocardial infarct size [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%